Remote Work Revolution in Strategic Human Resource Management: Identifying and Exploring Member Needs of a Geographycally-Dispersed Workforce - Eftimov, Lјupcho; Kitanovikj, Bojan (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2023)
Remote workspaces are an integral part of the future landscape of work. As more employees and gig workers are interested in working from a location other than the organizations’ offices, it is vital for human resource management to recognize why a potential member of the organization would prefer a particular location over others and how to manage team members who prefer working remotely. Understanding member needs goes a long way towards achieving this. Yet, the number of published studies that try to understand the basic needs of remote workers is low; studies exploring the business context of North Macedonia and the Western Balkan countries in general are even scarcer. In this research paper, our objective is to discover and investigate remote member’s needs in the digital workplace, structured through the lens of the self-determination theory. The research was conducted in North Macedonia, and we collected data through semi-structured interviews with remote employees who work in North Macedonia as a qualitative research approach. 24 member needs for the remote workplace were defined and categorized. The research makes an effort to contribute to the existing literature on remote work by addressing the significance and identification of member needs of remote workers, which can help human resource professionals humanize the digital workplace.
Keywords: Remote work; Member need; Self-determination theory